Analisis Pemahaman Konsep Vektor pada Siswa Sekolah Menengah Atas - Sari, Witri Puspita; Suyanto, Eko; Suana, Wayan (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2017)
Penelitian ini bertujuan untuk mengungkap pemahaman konseptual tentang vector, siswa kelas XI SMA di Kabupaten Natar, Lampung Selatan. Populasi adalah seluruh siswa kelas XI SMA dari tujuh SMA dan jumlah sampel sebanyak 167 siswa. Data dikumpulkan dengan menggunakan 15 soal pilihan jamak dan alasan pertanyaan yang dibutuhkan. Hasil penelitian menunjukkan bahwa hanya 39,1% siswa yang mengerti tentang konsep vektor. Vektor satuan adalah subtopik yang paling mudah dipahami dimana 61,1% siswa memahami subtopik sedangkan arah vektor adalah subtopik yang paling sulit bagi siswa dimana hanya 23,3% yang mengerti subtopic.Vectors Concepts Understanding Analysis on Junior High School StudentsThis research aims to reveal the students’ conceptual understanding about the vector of XI grade senior high school students in Natar district, South Lampung. The population was all of the students of XI grade from seven high schools, and the number of samples was 167 students. The data collected by using 15 multiple choice and reasons required questions. The results showed that only 39.1% students understood about vector concept. Unit vector was the most understandable subtopic where 61.1% of students understand the subtopic whereas the direction of the vector was the most challenging subtopic for students where only 23.3% understand the subtopic.